Theoretical study on rotating casson fluid in moving channel disk - Zulkhibri, Ismail; Ahmad Qushairi, Mohamad; Sharidan, Shafie; Nurul Aini, Jaafar; Qasim, Muhammad (Institute of Physics Publishing, 2019)
The theoretical study of rotating Casson fluid in moving channel disk has been investigated in this article. The dimensional governing equation of proposed fluid is derived in the form of partial differential equation with initial and boundary conditions. The non-dimensional governing equation has been obtained by using the suitable non-dimensional variables. The expression of velocity for rotating Casson fluid has been obtained by using Laplace transform method. It is found that they satisfied governing equation and conditions imposed. Computations are carried out and the results are analyzed and discussed in details.